ANALISIS PENURUNAN TANAH TIMBUNAN PADA BENDUNGAN PIDEKSO MENGGUNAKAN ALAT TOTAL STATION DAN INSTRUMENTASI (INCLINOMETER) - Agus, Agus Puji Utomo; Tri Nalasrsih, Retno; Ristanto, Iwan (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
Pidekso Dam is a dam on the Bengawan Solo River, located in Giriwoyo District Wonogiri Regency. According to the Directorate General of Water Resources and the Ministry of PUPR, the Pidekso Dam is one of the national strategic projects (PSN) which is targeted for completion in 2021. As a new dam, reducing the dam's embankment is something that needs to be paid attention to and monitored periodically. This research was conducted to determine the decline in the Pidekso Dam stockpiles after it was inaugurated within a period of 7 months, namely from January 2022 to July 2022. The method used in this research is observing surface movement monuments using a total station and observing settlement using Inclinometer instrumentation. The results of this research are that there has been a decrease in embankment at Pidekso Dam, both according to observations with a total station and observations with an inclinometer. Based on the results of observations, the average decline in Pidekso Dam through observations of surface movement monuments value is -0.047 m compared to observations using inclinometer is -0.039 m. However, the difference in the average value of the decrease is not too big.